Estudo da geometria do cavaco no corte com discos abrasivos - Bianchi, Eduardo Carlos [UNESP]; Da Silva, Eraldo Jannone [UNESP]; De Domenico Valarelli, Ivan [UNESP]; De Aguiar, Paulo Roberto [UNESP] (My University, 2001)
This paper shows a research about the study of the chip's geometry generated in the diving cut-off operation, under several cutting conditions. As a result it was possible to verify tint the cutting conditions and the type of the material being cut can directly affect the chip's geometry.
The study of the chip's geometry when cutting with abrasive disc
Keywords: Chip's geometry; Cut-off operation; Cutting conditions